PENGARUH PENGALAMAN, KEAHLIAN, DAN SKEPTISISME PROFESIONAL TERHADAP PENDETEKSIAN KECURANGAN (STUDI EMPIRIS PADA BPK RI PERWAKILAN SUMATERA SELATAN) - Indri Ningtyas; Harun Delamat; Emylia Yuniartie (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2018)
This research was aimed to examine the effect of experience, expertise,and professional skepticism toward fraud detection empirical study in BPK RI South Sumatra Representative. The research uses independent variables is experience, expertise and professional skepticism. The dependent variabels are fraud detection. The population of this study is all of the auditors working at BPK RI South Sumatra Respresentative. The samples was conducted by total sampling. For collecting data, the writer uses questionnaires.The Data Analysis uses a multiple linear regressions using the Statistical Packages for Social Science (SPSS) version 21. The statistical method which is used to test the hypothesis is multiple linear regression analysis. The result showed that experience and expertise have a influence on fraud detection. Variable professional skepticism have no influence on fraud detection.